Mitochondrial DNA copy number and D-loop region methylation in carriers of amyotrophic lateral sclerosis gene mutations. (8th August 2018) - Stoccoro, Andrea; Mosca, Lorena; Carnicelli, Vittoria; Cavallari, Ugo; Lunetta, Christian; Marocchi, Alessandro; Migliore, Lucia; Coppedè, Fabio
Aim: To investigate mitochondrial DNA (mtDNA) copy number and D-loop region methylation in carriers of SOD1, TARDBP, FUS and C9orf72 mutations.Methods: Investigations were performed in blood DNA from 114 individuals, including amyotrophic lateral sclerosis (ALS) patients, presymptomatic carriers and noncarrier family members.Results: Increased mtDNA copy number (p = 0.0001) was observed in ALS patients, and particularly in those with SOD1 or C9orf72 mutations. SOD1 mutation carriers showed also a significant decrease in D-loop methylation levels (p = 0.003). An inverse correlation between D-loop methylation levels and the mtDNA copy number (p = 0.0005) was observed.Conclusion: Demethylation of the D-loop region could represent a compensatory mechanism for mtDNA upregulation in carriers of ALS-linked SOD1 mutations.